Dynamic changes in fungal communities and functions in different air-curing stages of cigar tobacco leaves - Zhao, Songchao; Li, Yuanyuan; Liu, Fang; Song, Zhaopeng; Yang, Weili; Lei, Yunkang; Tian, Pei; Zhao, Mingqin (Frontiers in Microbiology, 2024)
Introduction Air curing (AC) plays a crucial role in cigar tobacco leaf production. The AC environment is relatively mild, contributing to a diverse microbiome. Fungi are important components of the tobacco and environmental microbiota. However, our understanding of the composition and function of fungal communities in AC remains limited. Methods In this study, changes in the chemical constituents and fungal community composition of cigar tobacco leaves during AC were evaluated using flow analysis and high-throughput sequencing. Results The moisture, water-soluble sugar, starch, total nitrogen, and protein contents of tobacco leaves exhibited decreasing trends, whereas nicotine showed an initial increase, followed by a decline. As determined by high-throughput sequencing, fungal taxa differed among all stages of AC. Functional prediction showed that saprophytic fungi were the most prevalent type during the AC process and that the chemical composition of tobacco leaves is significantly correlated with saprophytic fungi. Conclusion This study provides a deeper understanding of the dynamic changes in fungal communities during the AC process in cigar tobacco leaves and offers theoretical guidance for the application of microorganisms during the AC process.